Employee Development Strategies to Enhance Organizational Performance - Andi Ibbar (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This article discusses the critical importance of employee development as a strategic approach to enhance organizational performance. In an increasingly competitive business environment, organizations must prioritize the growth and development of their workforce to maintain a competitive edge. By identifying specific training and development needs, organizations can create tailored programs that effectively improve employees' skills, knowledge, and competencies. This research employs a qualitative approach, utilizing case studies from several companies in Indonesia to explore various employee development initiatives and their impact on organizational outcomes. The findings indicate that investing in employee development not only enhances individual performance but also contributes significantly to the overall achievement of organizational goals. Furthermore, the study highlights the role of leadership, mentoring, and the integration of technology in facilitating effective employee development strategies. Ultimately, this research underscores the necessity for organizations to adopt comprehensive employee development practices to foster a culture of continuous improvement and engagement.